1998
DOI: 10.1016/s0014-5793(98)00073-8
|View full text |Cite
|
Sign up to set email alerts
|

Heparin inhibits phorbol ester‐induced ornithine decarboxylase gene expression in endothelial cells

Abstract: Glycosaminoglycans regulate angiogenesis by affecting the availability of different growth factors for the endothelial cell (EC). However, little is known about the molecular and functional consequences resulting from direct interaction of these polyelectrolytes with the EC. Here we show that heparin markedly inhibited serum-stimulated DNA synthesis and ornithine decarboxylase (ODC) mRNA expression in human endothelial cells (HEC). About 50% of the serum effect on DNA synthesis and ODC gene expression was prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Finally, the cells were digested by the addition of 25 m formic acid (500 µL). Each formic acid digest was transferred with one rinse of NaCl/P i (1 mL) to a scintillation vial containing 3.5 mL of INSTA‐GEL scintillation fluid (Packard instrument Co., Meriden, CT, USA), and radioactivity was determined by liquid scintillation counting using a Wallac 1215 RackBeta liquid scintillation counter (LKB Instrument Inc., Gaithersburg, MD, USA) [16].…”
Section: Determination Of Dna Synthesismentioning
confidence: 99%
“…Finally, the cells were digested by the addition of 25 m formic acid (500 µL). Each formic acid digest was transferred with one rinse of NaCl/P i (1 mL) to a scintillation vial containing 3.5 mL of INSTA‐GEL scintillation fluid (Packard instrument Co., Meriden, CT, USA), and radioactivity was determined by liquid scintillation counting using a Wallac 1215 RackBeta liquid scintillation counter (LKB Instrument Inc., Gaithersburg, MD, USA) [16].…”
Section: Determination Of Dna Synthesismentioning
confidence: 99%
“…2C, D). We have previously shown that heparin failed to abolish completely the serum‐stimulated DNA synthesis in HEC and that the effect of the polyelectrolyte occurred by the inhibition of a serum‐activated PKC‐dependent pathway [21]. Here, we investigated whether such a signalling mechanism may also be involved in the induction of PKC genes.…”
Section: Resultsmentioning
confidence: 96%
“…Consonant with growth inhibition, heparin inhibits the expression of the early proto‐oncogenes c‐fos and c‐myc by acting selectively on a PKC‐dependent pathway [18–20]. The inhibition of this signalling pathway was also found to be the mechanism by which heparin down‐regulated the ODC gene expression and cell proliferation in EC [21]. It is increasingly becoming evident that PKC isoenzyme gene expression, besides enzyme activity, may elicit complex cellular responses.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations